Utilization of PET bottles and plastic granules in geopolymer concrete. (2021) - Chithambar Ganesh, A.; Deepak, N.; Deepak, V.; Ajay, Sidhu; Pandian, Arun; Karthik,
Abstract: This research work investigates the utilization of plastic wastes in the form of Polyethylene terephthalate (PET) bottles. PET bottles are used as a whole bottles inside geopolymer concrete specimen in proportions such as 3, 6 and 12. PET bottles are shredded and crushed to fine powder and are used as a partial replacement of M-sand in proportions such as 5, 10 and 15 percent. The novelty of this work lies in the utilization of PET bottles in geopolymer concrete. In this research, works have been focused to develop pervious geopolymer concrete using Ground Granulated Blast Furnace Slag as the base material. Combination of sodium hydroxide and sodium silicate solution was used as the alkaline activator solution. Properties such as workability, compressive strength, tensile strength and water absorption are determined in this work. Also effort has been made to analyze the behavior of specimen embedded with plastic at elevated temperatures such as 200, 400, 600 and 800 °C. This research unleashes the scope of utilization of waste plastics inside sustainable geopolymer concrete.